Social Conflict In Margot Lee Shetterly’s Hidden Figures Novel - Sembiring, Elita Modesta; Simamora, Nurlaidy Joice; Sinaga, Rosenta (Formosa Journal of Applied Sciences, 2024)
The purposes of this study to find out the kinds of social conflicts exist Hidden Figures Novel and to describe how the impact of the social  conflicts on characters such as Dorothy Voughan, Marry Jackson, Katherine Jhonson, Christina Darden and the other black people character in this novel. The data in this research  part of the novel that is related to the social conflict. The source of data comes from the novel Hidden Figures. The method of the research is descriptive qualitative research. By using the Soerjono Soekanto’s theories (2017). He stated there are five kinds of social conflict. The five social conflict are conflict of an International Nature, Political conflicts, conflicts between social classes, Racial conflicts, and Personal conflict. Then there are five impacts of social conflict in his theory.